The Unity of Acts “Tawhid Afa'ali” in the Light of the Unity of Being “Wahdat al-Wujud” from the View of Aqa Ali Modarres - Muhammad Reza Ershadinia (آموزه‌‌های فلسفه اسلامي, 2019)
The insight based on Tawhid (Unity of Allah) and believing in Tawhid is the fruitful core of the action and reaction of the monotheists. All monotheists' growth and movement will pivot based on this axis. Scholastic theologians of Islam (mutakallimun) in the theological procedures have gradually argued Tawhid in essence (dhat) and attributes and God's acts and have strengthened the theological purposes by it. Islamic philosophers have analyzed Tawhid issue with different bases and methods and with innovation have left deep matters. In their powerful look, the essence of Tawhid is sincerity (al-ikhlas) and it should be revealed in all actions and reactions of the monotheists. The Unity of acts (Tawhid afa'ali) is the title which contains this meaning. Islamic philosophers with this title are going to determine the proportion of the effects and acts to contingency (mumkin) and a necessity (wajib) in relation to real longitudinal not latitudinal or figurative relating to both parties. Among this, muta'li philosophers with considering Tawhid criterion obtained from the revelation prophets have transcended the longitudinal ratio and with the criterion of a mediating position between determinism -fatalism- and absolute free will (al-amr bain al-amrain) and with observing Unity of Being (Tawhid wujudi) have established a new position. In this regard, Hakim Aqa Ali has stated his concern about Tawhid in Resale-E-Tawhidiyeh with the high and ingenious statement. In addition to the book “Badayi' al-Hekam” which he has written about the principles of the Unity of Being (Tawhid wujud) in details, in this brief paper, he has skillfully studied the principles which are leaded to the Unity of acts (Tawhid afa'ali). Through this, every of the general Tawhid, special Tawhid and more special (particular) Tawhid has a special position for him not to be mingled together the lowest with highest. The deliberate analysis in his Tawhid attitudes in addition to remove the accusation of his opposition to the Unity of being (Tawhid wujud) help to get high understanding of Tawhid teaching.